Paradiplomacy on Sustainable Water Optimization: An Analysis of the Cooperation between the Malang City Government and United States Agency for International Development (USAID) in the USAID-IUWASH TANGGUH Project - Sholihah, Nurur Rahmah Nia; Prinanda, Devita (Universitas Negeri Surabaya, 2024)
This study examines the implementation of the Malang City Government's cooperation with USAID in the IUWASH Tangguh program in the framework of paradiplomacy. This study uses a qualitative research method. Data were obtained from the actors involved and policy documents. Data collection techniques were carried out through interviews, observations, and review of policy documents. The findings of this study indicate that the paradiplomacy strategy in improving water security is quite positive, referring to increasing public access to drinking water in Malang City. Previously determined roles and tasks bound the cooperation within the USAID IUWASH Tangguh program. Cooperation is not carried out in the form of material assistance but in the form of improving the quality of Human Resources of the actors involved in clean water security. This paradiplomacy strategy aligns with and supports the Indonesian Government's plan to accelerate the achievement of the 100% Access to Safe Drinking Water target by 2026.